A push towards decentralised online social networks for an enhanced future digital economy. (Research'eu results magazine)
Online social networking (OSN) sites are reshaping the internet's structure, design and utility. An EU initiative targeted a push away from centralised services towards totally decentralised systems for positive change in the future provision of online social services.